Hungarian Monitoring, 10 June 1989 . [Magyar rádiófigyelő], 1989. június 10 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Wave of arrests in China - Paris press opinions on the rehabilitation of Imre Nagy - Jaruzelski's London visit - Political situation in Poland today - FRG awaits Gorbachev Domestic Affairs: - Opposition Roundtable and government representatives sign agreement to start talks - Károly Grósz at a rural Party meeting on the danger of a Party split - Reburial: conversations about 1956, and the historical role of Imre Nagy - Whoever is poor is poorest – conversation with sociologist Ottilia Solt Külpolitika: - Kínában letartóztatási hullám bontakozott ki - Párizsi lapvélemények NAGY Imre rehabilitálásáról - Jaruzelski londoni látogatása - A mai lengyel politikai helyzet - Az NSZK-ban várják Gorbacsovot Belpolitika: - Aláírták a megállapodást az EKA és a kormány képviselői a tárgyalások megkezdéséről - Grósz Károly a pártszakadás veszélyéről egy vidéki pártértekezleten - Az újratemetés eseményének kapcsán beszélgetések 56-ról, Nagy Imre történelmi szerepéről - Aki szegény, az a legszegényebb - Beszélgetés Solt Otília szociológussal